Fish and mercury: Influence of fish fillet culinary practices on human risk. (February 2016) - Mieiro, C.L.; Coelho, J.P.; Dolbeth, M.; Pacheco, M.; Duarte, A.C.; Pardal, M.A.; Pereira, M.E.
Abstract: The influence of different culinary practices (boiling, frying, grilling) and seasoning (salt, lemon, combined) on the Hg levels (total and organic) found in three marine fish species ( Scomber scombrus, Dicentrarchus labrax, Aphanopus carbo ) was evaluated. Cooking affected the Hg levels in a species-dependent manner. With the exception of D. labrax, T-Hg decreased in grilling and frying, while O-Hg decreased in all culinary practices. For all species, some Hg was also found in the boiling water. Since O-Hg is the major portion of Hg in fish muscle and all culinary practices removed O-Hg, setting consumption thresholds in terms of T-Hg in raw tissue seems protective and adequate. S. scombrus and D. labrax emerge as healthier and safer choices, while moderate consumption of A. carbo is recommended. These findings reinforce the need to maintain FAO/WHO's recommendation that vulnerable groups should eat less than 100 g of predatory species per week. Highlights: Cooking affected the Hg levels in a species-dependent manner. T-Hg decreased in grilling and frying practices. For all species, Hg was also found in the boiling water. O-Hg decreased in all culinary practices. Setting guidelines in terms of T-Hg in raw tissue seems protective and adequate.